Photoelectro-Fenton system including electromagnetic induction electrodeless lamp and black carbon poly tetra fluoro ethylene air-diffusion cathode: Degradation kinetics, intermediates and pathway for azo dye. (August 2020) - Kong, Jijie; Huang, Wen; Yang, Shaogui; He, Huan; Sun, Cheng; Xian, Qiming; Jiang, Dong
Abstract: The role of illumination and cathode is important to improve the efficiency of photoelectro-Fenton (PEF) system. In this study, cathodes with black carbon-poly tetra fluoro ethylene (BC-PTFE) for increase the concentration of hydrogen peroxide in PEF. A new PEF system using EIEL and BC-PTFE air-diffusion cathode was established. The electrode performance was tested and the influence factors, degradation kinetics, intermediates, pathway and mechanism of the model compound methyl orange (MO) were studied. The capacities of concentration decays and total organic carbon (TOC) removals were compared between different electrochemical advanced oxidation processes. The experimental conditions were optimized for a current density of 20 mA cm −2 with 0.5 mM Fe 2+ and 100 mg L −1 MO at 20 °C and pH 3.0 in an 8 L reservoir. The higher MO concentration was, the smaller pseudo-first-order kinetic constants of concentration decays and TOC removals were. Intermediate products were identified by gas chromatography-mass spectrometry and ion-exclusion high performance liquid chromatograph in EIEL-PEF. Combined with frontier electron density, the degradation pathway was deduced as follows: destruction of azo bond, substitution of OH, dehydrogenation and oxidation, opening-ring and mineralization. In EIEL-PEF, the concentration of oxalic acid and oxamic acid reached the maximum value 9.2 and 1.5 mg L −1 at 60 and 90 min, respectively. The photolysis of N-intermediates produced NH4 + -N was released in more proportion than NO3 − -N and oxamic acid-N. The study indicated that PEF system has the potential to remove organic pollutants in aquatic environments. Graphical abstract: Image 1 Highlights: PEF system using EIEL and BC-PTFE air-diffusion cathode was established. EIEL had stronger ability to excite and cleavage H2 O2 than Hg lamp. Pseudo-first-order kinetic constants of EIEL-PEF were higher than those of Hg-PEF. Oxalic acid and oxamic acid were easily resolved by EIEL instead of Fenton reagent. NH4 + - N was released in larger proportion than NO3 − -N and oxamic acid-N.